Approaches and Perspectives of the Westward Spread of Traditional Chinese Medicine: A Case Study of the Radicis Chynae - Xi Gao (Chinese Medicine and Culture)
Some Western scholars have re-examined the concept of “Chinese medicine” and its knowledge system under the influence of global history research methods in recent years, in an attempt to understand the factors that led to the spread of Chinese medicine around the world, and what kind of Chinese medicine is constituted outside of China. Thus, researchers have studied the initial stage of traditional Chinese medicine (TCM)'s entry into the western world, tracing its roots and observing new knowledge systems formed in the process of cross-cultural communication. Responding to the research of Western scholars, this paper studies the Radicis Chynae (《中国根书简》 Letters on Chinese Root), a monograph written by Andreas Vesalius, a famous European anatomist who lived in the 16th century. The author of this article examined the understanding and interpretation of Chinese medicine by the European intelligentsia from 16th to 19th century, investigated the influence of the westward spread of TCM on the scientific revolution and medical progress in Europe, and analyzed its relationship with the rise of Sinology in Europe. This article discusses the knowledge interaction between Chinese medicine and the formation of modern European medicine from the perspective of global history and cross-culture.